Motivation In Learning a Foreign Language - Islamova Tohira Rihsibayevna (Genius Journals, 2021)
In this article, motivation in learning a foreign language is considered. External and internal motivation types are analyzed as basic types. A narrow-minded external motivation determines the attitude towards mastering a foreign language as a way of selfaffirmation, and sometimes as a path to personal well-being. Intrinsic motivation is not associated with external circumstances, but directly with the object itself. It is also often called procedural motivation. All these issues are considered in the article thoroughly.
Keywords: Motivation in learning; external motivation; internal motivation; self-affirmation